Built environment correlates of objectively-measured sedentary behaviours in densely-populated areas. (November 2020) - Koohsari, Mohammad Javad; Shibata, Ai; Ishii, Kaori; Kurosawa, Sayaka; Yasunaga, Akitomo; Hanibuchi, Tomoya; Nakaya, Tomoki; Mavoa, Suzanne; McCormack, Gavin R.; Oka, Koichiro
Abstract: Few studies examine associations between objectively-calculated neighbourhood built environment attributes and objectively-assessed sedentary behaviour in different geographical locations, especially in highly-populated environments. Additionally, no study, to our knowledge, has investigated associations between objective measures of neighbourhood built environment attributes and objectively-assessed sedentary behaviours in middle-aged adults, despite the fact that this is a critical stage of life when age-related functional decline begins. We examined the associations between neighbourhood built environment attributes with the total, and patterns of, objectively-assessed sedentary behaviours in a densely-populated area in Asia. Data from 866 adults (ages 40 to 64) living in Japan were included. Four classifications of sedentary behaviours, including daily total sedentary time, duration and number of long (≥30 min) sedentary bouts and breaks per sedentary hour, were estimated using hip-worn accelerometers. Individual (population density, availability of destinations, number of intersections, and distance to the nearest park) and composite (walkability and Walk Score®) neighbourhood built environment indices were calculated using geographic information systems. Covariate-adjusted multilevel linear mixed effects models were used to estimate the associations between the neighbourhood built environment attributes and sedentary behaviours. Population density and availability of destinations were positively associated with sedentary behaviours; however, the number of intersections was negatively associated with sedentary behaviours. No associations were observed between the distance to the nearest park and sedentary behaviours. There were positive associations between walkability and total sedentary time, and duration and the number of long sedentary bouts. Walk Score® was positively associated with total sedentary time and the number of long sedentary bouts. These findings suggest that urban design attributes supportive of walking (except for the number of intersections) may encourage sedentary behaviour among middle-aged adults living in densely-populated environments. Highlights: Availability of destinations was positively associated with sedentary behaviours. Walkability and Walk Score® were positively associated with sedentary behaviours. Walkable built environment attributes may negatively influence middle-aged adults' sedentary behaviours.